PENGOLAHAN SAMPAH LIMBAH RUMAH TANGGA SECARA MEKANIK DI KELURAHAN PRINGGO KUSUMAN, KECAMATAN GEDONG TENGEN KOTA YOGYAKARTA - Joko Waluyo (DHARMA BAKTI, 2018)
The clean environment in Pringgokusuman Village, Gedong Tengen District, Yogyakarta City is a dream of the community in the village. The KOTAKU (No Slum City) Program is being held in RW 22 in Pringgokusuman Village, this program was carried out in order to realize that the environment was clean in the area from household waste which had so far received less attention so that it had an impact on the unhealthy environment. The community service carried out aims designing appropriate technology for processing household waste so as not to pollute the environment in RW 22 in Pringgokusuman Village, Gedong Tengen District, Yogyakarta City. The implementation of this community service was on October 8, 2018 at the location of RW 22 Kampung Notoyudan, Pringgo Kusuman Village, Gedong Tengen District, Yogyakarta City. The activities included Debriefing the community about processing waste using mechanical devices, Maintenance of mechanical devices and debriefing of household waste which results in the environment becoming unhealt. The result of community service is the number of community attendance in accordance with what is expected to be 90% present and the community capable of operating mechanical machinery, caring for mechanical machinery and replacing engine parts if any part of the device is damaged.